Bilateral deficit in the countermovement jump and its associations with judo-specific performance - Kons, R. L.; Ache-Dias, J.; Gheller, R. G.; Bishop, C.; Detanico, D. (Research in Sports Medicine, 2023)
This study aimed to describe the bilateral deficit (BLD) during the countermovement jump (CMJ) in judo athletes and determine the relationship between the BLD and judo-specific performance. Fourteen male judo athletes participated. Athletes performed three specific judo tests, Maximal Sprint Speed Judo Test, Maximal Aerobic Speed Judo Test and Special Judo Fitness Test (SJFT), and double- and single-leg CMJ. The following CMJ variables were used: jump height (JH), mean (MPO) and peak (PPO) power output, peak force (PF), peak velocity (PV) and impulse (IMP). The Pearson`s or Spearman`s test were used (p < 0.05). The results show that the BLD is found in all CMJ parameters (20 to 31%). Negative correlations between first set of SJFTTT (total throws) and BLD in PF (r = -0.60; p= 0.022) and between the second set of SJFTTT and BLD in MPO (r= -0.74;p = 0.002), PV (r =-0.59;p = 0.025) and IMP (r =-0.55; p = 0.040) were found. Also, negative correlations between SJFTTT and the BLD in all CMJ parameters (r= -0.53 to -0.85; p < 0.05) were found. Higher values of BLD are related to poor SJFTTT performance.